Astragali Radix-Coptis Rhizoma Herb Pair Attenuates Atherosclerosis in ApoE-/- Mice by Regulating the M1/M2 and Th1/Th2 Immune Balance and Activating the STAT6 Signaling Pathway. (7th February 2022) - Li, Zhaoyu; Ma, Dufang; Wang, Yongcheng; Wu, Sijia; Wang, Lin; Jiang, Yuehua; Zhang, Yongjian; Li, Xiao
Abstract : Objective . Immune imbalance and the inflammatory response are associated with atherosclerosis (AS) progression. Astragali Radix and Coptis Rhizoma (ARCR) are an ancient and classic herb pair that is used in herbal medicines for the treatment of coronary heart disease. We focused on the effects and mechanisms of the ARCR herb pair attenuation of atherosclerosis in apolipoprotein E knockout (ApoE-/-) mice. Methods . ApoE-/- mice were fed a high-fat diet for 12 weeks to establish a model of AS. The ApoE-/- mice were randomly divided into a model group, simvastatin group (Simva), Astragali Radix group (AR), Coptis Rhizoma group (CR), Astragali Radix-Coptis Rhizoma group (ARCR), and Astragali Radix-Coptis Rhizoma + signal transducer and activator of transcription factor 6 (STAT6) inhibitor (AS1517499) group (ARCR + AS1517499). C57BL/6 mice were used as controls. Each group was administered the corresponding drugs, and mice in the model and control groups were given the same volume of normal saline once daily for 6 weeks. The body weights of the mice were observed regularly. The effect of the ARCR herb pair on lipid content in peripheral blood was evaluated using blood lipid tests. The levels of serum matrix metalloproteinase-9 (MMP-9), interleukins-12 (IL-12), IL-10, interferon- γ (IFN- γ ), and IL-4 were determined to assess inflammation. Oil Red O staining, Sirius Red staining, and immunohistochemistry were used to observe changes in plaque stability. Western blotting was used to assay M1/M2 macrophages, Th1/Th2 cells, and STAT6 signaling pathway protein expression. Flow cytometry and immunofluorescence were used to detect M1/M2 macrophages and Th1/Th2 cells and reflect the immune imbalance. Results . The ARCR herb pair significantly reduced blood lipids levels and plaque vulnerability and regulated the levels of inflammatory factors and the number of M1/M2 macrophages and Th1/Th2 cells in ApoE-/- AS mice. It also decreased iNOS and T-bet protein levels and increased the Arg-1 and GATA-3 protein levels. The ARCR herb pair also increased STAT6 phosphorylation. A STAT6 inhibitor attenuated the regulation of M1/M2 and Th1/Th2 markers induced by the ARCR herb pair. Conclusion . The ARCR herb pair regulates blood lipid metabolism and attenuates atherosclerosis via regulation of M1/M2 and Th1/Th2 immune balance, which is achieved partially by increasing STAT6 phosphorylation. Our study provides new evidence for the possible use of ARCR herb pair in the prevention and treatment of AS.